Learning Methods Tahfidz Al-Qur’an Leading Class Program in Madrasah Tsanawiyah Islamiyah Blingoh - Rohmawati, Ummi; Az Zafi, Ashif (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
Islamic religious education is very important for every individual who is Muslim. Each madrasa teaches Islamic religious education to produce good and quality graduates. In memorizing al-Qur'an, a proper method is needed so that the memorizer is not only memorized but is able to recite verses with the correct machroj. The research was carried out by field research through interviews with the teachers of Tahfidz Qur'an and the principal of Madrasah Tsanawiyah Islamiyah Blingoh. The research aims to determine how the learning process, the learning methods applied, and the factors that support and hinder students in carrying out the Tahfidz learning process. This can be seen from the attention and efforts of the ustadz who guide and guide students in memorizing the Qur'an. In the learning Tahfidz Qur'an, there are things that must be considered, namely arranging the intention to seek the pleasure of Allah SWT. The methods used in the Tahfidz Qur'an learning are Bin-Nadhar, talaqqi, tahfidz and murojaah. During the process of Tahfidz activities, there are supporting factors for students in the learning process, such as motivation, careful self-preparation, age factors, timing, potential for memory and intelligence as well as a comfortable place to memorize. In addition, it is a factor that hinders students from carrying out the learning process. Namely, lack of self-motivation to memorize, lack of interest in talents, commit actions that lead to sinful acts, and decreased physical health.